Agricultural dust explosions in 1996 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 13 dust explosions reported in the U.S. in 1996 according to Robert W. Schoeff, Professor Emeritus, Kansas State University and Ralph Reg an, Safety Director, USDA-FGIS. This compares to 14 in 1995 and a ten-year average of 13 explosions.
Keywords: Grain dust; Dust explosions